Orientation and Type of Non-dental Glass Fiber Towards The Flexural of Fiber Reinforced Composite - Etny Dyah Harniati; Widjijono Widjijono; Rini Dharmastiti (Indonesian Journal of Dentistry, 2021)
Introduction : Non-dental glass fiber can used as alternative dental glass fiber. Flexural strength to withstand masticatory loads that influenced by various factors, including the orientation and type of fiber used. Purpose : The purpose of this study was to see the effect of orientation and type of non-dental glass fiber on flexural strength. Method : The research method used FRC samples measuring 65 x 10 x 2,5 mm which were reinforced with non-dental glass fiber mats, roving, woven roving, and dental glass fiber roving. Non-dental glass fiber mats and woven roving was cut according to the length and width of the sample, while the non-dental glass fiber roving was weighed according to the weigh tof 4 sheets of dental glass fiber roving to meet the sample mold zone. Result : Glass fiber placed in the tension position in the sample mold. The flexural strength was tested using universal testing machine. This study indicate that the type of glass fiber doesn’t have a significant effect on the flexural strength of FRC with reinforced non dental glass fiber and dental glass fiber. Conclusion : The orientation of non-dental glass fiber roving as reinforcement of FRC has greater flexural strength than non-dental glass fiber with mats and woven roving orientation.